Durability of steel reinforced polyurethane-to-substrate bond. (15th November 2018) - De Santis, Stefano; Stryszewska, Teresa; Bandini, Simone; de Felice, Gianmarco; Hojdys, Łukasz; Krajewski, Piotr; Kwiecień, Arkadiusz; Roscini, Francesca; Zając, Bogusław
Abstract: Steel reinforced polyurethane (SRPU) is an innovative composite material which comprises a unidirectional steel textile and a polyurethane matrix. By the virtue of the high flexibility of the polyurethane, which redistributes the shear stresses between reinforcement and substrate, SRPU has recently proved effective for specific externally bonded strengthening applications. The long-term SRPU bond performances, however, have not been sufficiently investigated to date. Nevertheless, they are of the utmost importance for mitigating the risks and the costs associated to damage and repair/substitution in the long-term. This is crucial for the sustainability of the building stock and of the rehabilitation measures developed for its lasting safeguarding. In this work, the durability of the bond of SRPU applied to masonry substrates was investigated. Single-lap shear bond tests were carried after drying, immersion in alkaline or substitute ocean water solutions, exposure to high humidity, and freeze-thaw cycles. Bond tests and SEM and EDS analyses showed that artificial aging did not generally affect the SRPU bond performance. The zinc coating, however, proved sensitive to the prolonged attack of alkali, which modified the interface between steel cords and polyurethane, suggesting the need of protecting the fabric by a complete covering with the matrix.